Recycling and re-use of waste rubber - Forrest, Martin (Smithers Rapra Technology Ltd, 2014)
The environmental and economic need to increase recycling rates is a principal driving force behind technological innovation in the 21 st century. Waste rubber products are an important resource that the global community is focusing on to achieve vital improvements in sustainability and meet important life cycle goals. . This comprehensive review, with extensive up-to-date referencing, covers all aspects of rubber recycling, from its world market to the many novel technologies and processes that have been developed to re-use the material to manufacture added-value products. . One objective of.
Keywords: Rubber -- Recycling.; Rubber, Reclaimed.; elektronické knihy; electronic books